Membrane Assisted Simultaneous Extraction and Derivatization with Triphenylphosphine of Elemental Sulfur in Arabian Crude Samples by Gas Chromatography/Mass Spectrometry - Ibrahim Al-Zahrani; Munzir H. Aneel Mohammed; Chanbasha Basheer; Mohammad Nahid Siddiqui; Abdulrahman Al-Arfaj (Journal of Chemistry)
Determination of trace level elemental sulfur from crude oil samples is a tedious task. Recently, several gas chromatographic methods were reported in which selective triphenylphosphine derivatization of sulfur was used to form triphenylphosphine sulfide. Direct quantitation of elemental sulfur from crude oil requires an efficient sample preparation method. This paper describes how simultaneous extraction derivatization of elemental sulfur was performed for the first time using porous hollow fiber membrane. A thick (0.25 um pore size; 1550 μm wall thickness; and 5500 μm inner diameter) hollow fiber membrane filled with triphenylphosphine (dissolved N-methylpyrrolidone) is used as a solvent bar. The solvent bar is tumbled freely in the crude oil sample; the elemental sulfur was extracted and derivatized. Finally, the derivatized sulfur was analyzed by gas chromatography/mass spectrometry. Various experimental conditions of solvent bar microextraction (SBME) were optimized to achieve higher extraction. The linear range was established between 1 and 50 μg/mL, while a squared regression coefficient was found to be 0.9959 μg/mL. Relative standard deviation (RSD) was below 10%. Relative recoveries were calculated for SBME in crude oil samples and were in the range between 98.2% and 101.2%.